Correlative tomography and authentication features of a shrunken head (tsantsa) - Lauren September Poeta; Maria Patricia Ordóñez; Eric Fournier; Andrew John Nelson (PLoS ONE, 2022)
Museum personnel and the general public have become quite familiar with the presence of shrunken heads in museum collections, but the procedures to authenticate the history and origin of these unique cultural items are not yet reliable. These shrunken heads, called tsantsas, are meant to be the cultural material remains of ceremonies conducted by the Shuar and Achuar Peoples of South America. This project seeks to integrate the use of micro-computed tomography (micro-CT) scanning with methods used in previous studies (clinical computed tomography (CT) and visual inspections) to examine authentication procedures of shrunken heads (tsantsas) held in contemporary museum collections. We use a correlative tomographic approach using several scans at successively higher resolutions to determine whether a tsantsa was created from human remains, and if so, what key features can best contribute to its authentication. Conclusively, our correlative tomographic approaches provide new insights into the determination process of whether a tsantsa was created from real human remains or not. Also, this study questions whether the previously conceptualized dichotomy of ceremonial or commercial might be better thought of as a continuum of practice. Investigating and redefining the examination and authentication procedures of tsantsas is crucial for future ethical curation, management, and repatriation efforts of this unique cultural material of the Shuar and Achuar Peoples.